Alexithymia and emotion regulation - Preece David A.; Mehta Ashish; Petrova Kate; Sikka Pilleriin; Bjureberg Johan; Becerra Rodrigo; Gross James J. (Elsevier, 2023)
Background
Alexithymia is a key transdiagnostic risk factor for emotion-based psychopathologies. Conceptual models specify that this is because alexithymia impairs emotion regulation. However, the extent of these putative emotion regulation impairments remains underexplored. Our aim in this study was to begin to address this gap by examining whether people with high, average, or low levels of alexithymia differ in the types of emotion regulation strategies they typically use.
Method
General community adults from the United States (N = 501) completed a battery of alexithymia and emotion regulation measures. Participants were grouped into high, average, and low alexithymia quantiles.
Results
After controlling for demographics and current levels of distress, the high, average, and low alexithymia groups differed in their use of cognitive and behavioral emotion regulation strategies. Compared to the other groups, the high alexithymia group reported lesser use of generally adaptive regulation strategies (cognitive reappraisal, approaching problems, and seeking social support) and greater use of generally maladaptive regulation strategies (expressive suppression, behavioral withdrawal, ignoring).
Limitations
Our data were cross-sectional and from self-report questionnaires. Future work in other cultural groups would be beneficial.
Conclusions
Our results support the view that alexithymia is associated with impaired emotion regulation. In particular, people with high alexithymia seem to exhibit a less adaptive profile of emotion regulation strategies. Direct targeting of these emotion regulation patterns in psychotherapy may therefore be a useful pathway for the treatment of emotional disorder symptoms in people with high alexithymia.